Evidence for suppression of parathyroid gland activity by hypermagnesemia - Massry, Shaul G. (1970)
The effect of hypermagnesemia, produced by MgCl(2) infusion, on the activity of parathyroid glands, as assessed by changes in levels of serum calcium (S(Ca)) and in the fraction of filtered phosphate excreted (C(P)/C(Cr)), was studied in 11 intact and 4 thyroparathyroidectomized (T-PTX) dogs. To exclude the effect of diurnal variation in C(P)/C(Cr) on the results, studies were initiated in both morning and afternoon hours and each study with MgCl(2) infusion was paired with a control experiment in the same dog not receiving MgCl(2). During MgCl(2) infusion, serum phosphorus rose progressively. Despite this rise, the levels of C(P)/C(Cr) fell in all experiments and were significantly different from values observed at the same time of the day in the paired control experiments. The concentrations of total S(Ca) fell by 1.0-2.4 mg/100 ml with a proportional decrease in the levels of the diffusible and ionized fractions. The pattern of the fall in C(P)/C(Cr) during MgCl(2) resembled that observed after CaCl(2) infusion (seven dogs) and that which acutely followed thyroparathyroidectomy (seven dogs). When parathyroid extract was given to dogs receiving MgCl(2) infusion both C(P)/C(Cr) and S(Ca) rose, and MgCl(2) infusion did not affect C(P)/C(Cr) and S(Ca) in T-PTX dogs. These results indicate that hypermagnesemia suppresses the activity of the parathyroid glands, probably, by inhibiting production and (or) release of the hormone, without interfering with end-organ response. An increase in serum magnesium of 1.7-2.0 mg/100 ml was capable of producing the suppressive effect. Evaluation of the effect of simultaneous modest hypocalcemia and hypermagnesemia suggests that a decrease in the level of serum calcium is more potent than an increase in the concentration of serum magnesium in the regulation of parathyroid activity.